DEVELOPING SPEECH ABILITIES IN CHILDREN WITH HEARING IMPAIRMENTS IN THE EDUCATIONAL PROCESS AS AN IMPORTANT FACTOR IN PREPARING THEM FOR SOCIAL LIFE - Teshaboeva Feruza Rakhimovna (Bright Mind Publishing, 2025)
This article discusses the fact that in recent years the socialization of children with hearing impairments has become one of the most pressing issues in pedagogy, psychology, and sociology both in the Republic of Uzbekistan and abroad. The paper emphasizes that expanding the speech and sensory capabilities of children with hearing impairments contributes to the formation and development of their thinking. Since cognitive processes are closely interconnected with speech, their development simultaneously creates opportunities to enhance children’s speech, enrich their imagination, and familiarize them with the surrounding environment. As a result, the process of socialization of children with hearing impairments becomes easier and more effective.
Keywords: Children with hearing impairments, speech, sensory development, thinking, cognitive processes, imagination, socialization, adaptation.